The Potential Clash of Social Relationship between Muslim and Buddhist (Case Study on the Conflict of Buddha Statue in Tanjungbalai City, North Sumatra) - Irwansyah Irwansyah (Analisa: Journal of Social Science and Religion, 2013)
Socio-religious conflicts that occurred in Tanjungbalai City allegedly caused by the establishment of Buddha Statue. This research aims to reveal how relations between Muslim and Buddhist in Tanjungbalai. This study classified as qualitative research. Fact were obtained through observation, interviews, and document review. The results showed social conflict occurred after the establishment of Buddha Statue. Tanjungbalai as one of “China town”, to trigger the social jealousy. In addition to the economic factors are controlled by China,  Tanjungbalai City the majority of Muslims, did not accept the establishment of 6 metre tall Buddha Statue that was on the fourth floor of the building Vihara Tri Ratna. Muslims aliancy movement asking for removal of the statue. Buddhists being defensive and worried that the Malays (Muslims) think that the Buddhist same with “the Chinese”.